Spirituality in mathematics - Kessler, Volker 1962- (2019)
This paper is about spirituality in mathematics. In a phenomenological approach, I analyse spiritual experiences that some mathematicians have while doing mathematics. By analysing autobiographical notes from Western mathematicians of the 20th and 21st century, I conclude that there are four possible gateways by which spirituality can enter mathematics: (1) pragmatic Platonism; (2) aesthetics, that is, the role of beauty within mathematics; (3) the study of patterns; and (4) the role of inner understanding and inner vision. Examples show that even committed atheists experience spirituality in mathematical research in these terms.
Keywords: Aesthetics; Gateways; inner vision; mathematical beauty; Mathematics; patterns; Spirituality